Form, Function, and Geometric Morphometrics. Issue 1 (January 2015) - Cooke, Siobhán B.; Terhune, Claire E.; Terhune, Claire; Cooke, Siobhán B.; Laitman, Jeffrey T.
ABSTRACT Geometric morphometrics (GM) has increasingly become an important tool in assessing and studying shape variation in a wide variety of taxa. While the GM toolkit has unparalleled power to quantify shape, its use in studies of functional morphology have been questioned. Here, we assess the state of the field of GM and provide an overview of the techniques available to assess shape, including aspects of visualization, statistical analysis, phylogenetic control, and more. Additionally, we briefly review the history of functional morphology and summarize the main tools available to the functional morphologist. We explore the intersection of geometric morphometrics and functional morphology and we suggest ways that we may be able to move forward in profitably combining these two research areas. Finally, this paper provides a brief introduction to the papers in this special issue and highlights the ways in which the contributing authors have approached the intersection of GM and functional morphology. Anat Rec, 298:5–28, 2015. © 2014 Wiley Periodicals, Inc.